Abnormal Innate Immunity in Acute-on-Chronic Liver Failure: Immunotargets for Therapeutics - Khanam, Arshi; Kottilil, Shyam (Frontiers in Immunology, 2020)
Acute-on-Chronic Liver Failure (ACLF) is a severe life-threatening condition with high risk of multiorgan failure, sepsis and mortality. ACLF activates a multifaceted interplay of both innate and adaptive immune response in the host which governs the overall outcome. Innate immune cells recognize the conserved elements of microbial and viral origin, both to extort instant defense by transforming into diverse modules of effector responses and to generate long-lasting immunity, but can also trigger massive intrahepatic immune inflammatory response. Acute insult results in the activation of innate immune cells which provokes cytokine and chemokine cascade and subsequently initiate aggressive systemic inflammatory response syndrome, hepatic damage and high mortality in ACLF. Dysregulated innate immune response not only play a critical role in disease progression but also potentially correlates with clinical disease severity indices including Child- Turcotte-Pugh, model for end-stage liver disease and sequential organ failure assessment score. A better understanding of the pathophysiological basis of the disease and precise immune mechanisms associated with liver injury offers a novel approach for the development of new and efficient therapies to treat this severely ill entity. Immunotherapies could be helpful in targeting immune mediated organ damage which may constrain progression towards liver failure and eventually reduce the requirement for liver transplantation. Here, in this review we discuss the defects of different innate immune cells in ACLF which updates the current knowledge of innate immune response and provide potential targets for new therapeutic interventions.